2019
DOI: 10.1002/jsc.2258
|View full text |Cite
|
Sign up to set email alerts
|

The applicability of Porter's generic strategies in pure online firms: A case study approach

Abstract: The aim of this paper is to investigate the usability and applicability of Porter's generic strategies in the current e‐business environment. In this paper, a review of Porter's generic strategies was conducted to recognise the limitations and weaknesses of the model, which prevent its effective application in the e‐business environment. To do so, a case study approach on three pure online firms, e.g., Amazon, e‐bay and Google was employed. The findings acknowledged the application of Porter's generic strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 62 publications
(86 reference statements)
1
8
0
Order By: Relevance
“…Accordingly, H5 ( p -value < 0.005) and H6 ( p -value < 0.005) are supported. These results are parallel to Firoz Suleman et al (2019), Anwar (2018), Herzallah et al (2017) and are in agreement with the work of Cantele and Zardini (2018), Santos-Vijande et al (2012), Bayraktar et al (2017) and Li et al (2006), all showing partial agreement. In addition, it has been determined that there is a statistically positive and significant relationship between competitive strategies and market performance.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Accordingly, H5 ( p -value < 0.005) and H6 ( p -value < 0.005) are supported. These results are parallel to Firoz Suleman et al (2019), Anwar (2018), Herzallah et al (2017) and are in agreement with the work of Cantele and Zardini (2018), Santos-Vijande et al (2012), Bayraktar et al (2017) and Li et al (2006), all showing partial agreement. In addition, it has been determined that there is a statistically positive and significant relationship between competitive strategies and market performance.…”
Section: Discussionsupporting
confidence: 87%
“…With this strategy, it provides customers with standardized products and services at the most competitive prices so that firms can lower prices or beat their competitors and still make a profit (Santos-Vijande et al , 2012). Indeed, the main focus of the cost leadership strategy is to be able to put forward activities aimed at achieving sustainable competitive advantage by reducing and controlling costs (Firoz Suleman et al , 2019). With a cost-based strategy, a firm can increase profitability and market share with a lower cost structure (Koo et al , 2004).…”
Section: Theoretical Background and Research Hypothesesmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been determined that the focus strategy only affects the product-oriented performance. In the research conducted in companies that dominate the market in online commerce such as Amazon, E-bay and Google, it has been found that generic strategies are positively related to firm performance, but the differentiation strategy is more sustainable in the online market than the low cost leadership strategy (Suleman, Rashidirad, & Suleman, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, Thornhill and White (2007), based on 2,351 firms, found that firms with pure strategies outperformed those with hybrid strategies. Currently, studies are still discovering and confirming the applicability of pure strategies to firms in traditional sectors and manufacturing, such as the study of small and medium-sized agricultural firms in 12 Latin American countries (Brenes et al, 2020), and the three case studies of Amazon, eBay, and Google (Firoz Suleman et al, 2019).…”
Section: Theoretical Backgroundmentioning
confidence: 99%